LEO clinical update course on pediatric ophthalmology and strabismus - Wright, Kenneth W.; McKeown, Craig A.; Drack, Arlene V.; Repka, Michael X.; Ophthalmology Interactive ([San Francisco] : American Academy of Ophthalmology, 1998)
(Producer) Discusses the latest in common and important pediatric disorders, including ambloyia in preverbal children, pediatric ophthalmic infectious diseases, blindness in newborns, retinopathy of prematurity, esotropia and exotropia, and vertical strabismus and indications for surgery
Title from disc label
CD is available at Koleksi Media, Perpustakaan HUKM/ Perpustakaan Perubatan KL
Kenneth W. Wright, et al.
Keywords: Eye Diseases -- child; Eye Diseases -- infant